Cerebellar Calcium-Binding Protein and Neurotrophin Receptor Defects in Down Syndrome and Alzheimer's Disease - Miguel, Jennifer C.; Perez, Sylvia E.; Malek-Ahmadi, Michael; Mufson, Elliott J. (Frontiers in Aging Neuroscience, 2021)
Cerebellar hypoplasia is a major characteristic of the Down syndrome (DS) brain. However, the consequences of trisomy upon cerebellar Purkinje cells (PC) and interneurons in DS is unclear. The present study performed a quantitative and qualitative analysis of cerebellar neurons immunostained with antibodies against calbindin D-28k (Calb), parvalbumin (Parv) and calretinin (Calr), phosphorylated and non-phosphorylated intermediate neurofilaments (SMI-34 and SMI-32), high (TrkA) and low (p75NTR) affinity nerve growth factor (NGF) receptors as well as tau and amyloid in DS (n=12), Alzheimer’s disease (AD) (n=10) and healthy-non demented controls (HC) (n=8) cases. Our findings revealed higher APP/Aβ plaque load in AD and DS compared to HC, but no differences in Aβ42 plaque load between groups. Cerebellar cortex did not display Aβ40 nor pathologic phosphorylated tau in any case examined. Number and optical density (OD) measurements of Calb immunoreactive (-ir) PC soma and dendrites were similar between groups, while number of PCs positive for Parv and SMI-32 were significantly reduced in AD and DS compared to HC. By contrast, the number of SMI-34-ir PC dystrophic axonal swellings, termed torpedoes, were significantly greater in AD compared to DS. No differences in SMI-32 and Parv-ir PC OD measurement were observed between groups. Conversely, total number of Parv- (stellate/basket) and Calr (Lugaro, brush and Golgi)-positive interneurons were significantly reduced in DS compared to AD and HC. A strong negative correlation was found between counts for Parv-ir interneurons, Calr-ir Golgi and brush cells and Aβ42 plaque load. Numbers of TrkA and p75NTR positive PCs were reduced in AD compared to HC. These findings suggest that disturbances in calcium binding proteins play a critical role in cerebellar neuronal dysfunction in adults with DS.